2021
DOI: 10.1038/s41598-021-85066-z
|View full text |Cite
|
Sign up to set email alerts
|

A multifaceted approach to understanding bat community response to disturbance in a seasonally dry tropical forest

Abstract: Given widespread habitat degradation and loss, reliable indicators are needed that provide a comprehensive assessment of community response to anthropogenic disturbance. The family Phyllostomidae (Order Chiroptera) has frequently been the focus of research evaluating bats’ response to habitat disturbance in seasonally dry tropical forests (SDTFs). However, few studies compare this family to the larger bat assemblage to assess its efficacy as a bioindicator. We compared community and species-specific attributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 66 publications
1
6
0
4
Order By: Relevance
“…The species composition of bats was different between the two habitats, agreeing with other studies (Chambers et al., 2016; de Oliveira et al., 2017; Valle et al., 2021). These patterns could reflect the longer time that species composition takes to recover after disturbance (Dunn, 2004) or species‐specific differences related to food resources and home ranges (Chambers et al., 2016).…”
Section: Discussionsupporting
confidence: 91%
“…The species composition of bats was different between the two habitats, agreeing with other studies (Chambers et al., 2016; de Oliveira et al., 2017; Valle et al., 2021). These patterns could reflect the longer time that species composition takes to recover after disturbance (Dunn, 2004) or species‐specific differences related to food resources and home ranges (Chambers et al., 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Multiple studies have shown that the degradation process in SDTFs generate a significant loss of plant and animal biodiversity (see Gillespie et al 2000, Zúñiga-González et al 2000, Shahabuddin and Kumar 2006, Avila-Cabadilla et al 2009, Williams-Linera and Lorea 2009, Espinosa et al 2011, Falcão et al 2018, Valle et al 2021). In the case of plants, it has been proposed that the loss of diversity occurs as a result of increased stress caused by reduced coverage, which implies an increase in drought and solar incidence (Jara-Guerrero et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of plants, it has been proposed that the loss of diversity occurs as a result of increased stress caused by reduced coverage, which implies an increase in drought and solar incidence (Jara-Guerrero et al, 2021). In the case of animals, the mechanism that generates the loss of diversity is less clear, but it is assumed that the changes may be due to a higher difficulty of the individuals to exploit the most degraded areas (Ordóñez-Delgado et al, 2016;Valle et al, 2021). It was found that the occurrence of micronuclei and nuclear abnormalities increased with the level of forest degradation although noticeable interspecific differences in this relationship were found.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that the degradation process in SDTFs generates a significant loss of plant and animal biodiversity (see Avila‐Cabadilla et al., 2009 ; Espinosa et al., 2011 ; Falcão et al., 2018 ; Gillespie et al., 2000 ; Jara‐Guerrero et al., 2021 ; Shahabuddin & Kumar, 2006 ; Valle et al., 2021 ; Williams‐Linera & Lorea, 2009 ; Zúñiga‐González et al., 2000 ). In the case of plants, it has been proposed that the loss of diversity occurs because of increased stress caused by a reduction in tree coverage, which implies an increase in drought and solar incidence (Jara‐Guerrero et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%